C-reactive protein as a prognostic factor in patients with chordoma of lumbar spine and sacrum—a single center pilot study. Issue 1 (December 2016) - Hobusch, Gerhard; Bodner, Florian; Walzer, Sonja; Marculescu, Rodrig; Funovics, Philipp; Sulzbacher, Irene; Windhager, Reinhard; Panotopoulos, Joannis
Abstract Study design This is a retrospective, diagnostic study, level IV. Background It appears to be necessary to identify prognostic markers for individual risk estimation for progression and survival in patients with chordoma, a rare disease. Are pre-operative serum levels of C-reactive protein (CRP) associated with disease progression and survival? Methods Survival rates of 24 patients (18 males, 6 females) (mean age 67 years (SD ± 16; range 20–85 years); minimum follow-up 2 years, mean follow-up 5 years (SD ± 5; range 2–19 years)) with chordoma of the lower spine and sacrum were assessed with a focus on pre-operative CRP levels. Results The survival rate of patients with pre-operative CRP level of >1.0 mg/dl was lower than that of patients with a CRP level <1.0 mg/dl (p  = 0.01). The estimated 10-year survival of patients with pre-operative CRP values <1.0 and >1.0 mg/dl was 76 and 25 %, respectively. CRP remained as an independent survival factor (p  = 0.025; CI 95 % 1.0–2.6) in multivariable analysis. Conclusions Pre-operative CRP levels appear to be a biomarker for disease-specific survival in patients with chordoma of the lumbar spine and sacrum. A validation of our finding with larger cohorts and integration of putative risk factor would further elucidate CRP a surrogate for tumor progression.